The VALUES OF CHARACTER EDUCATION IN MONOLOGUES TANGAN KECIL AINI: NILAI-NILAI PENDIDIKAN KARAKTER DALAM NASKAH MONOLOG TANGAN KECIL AINI - Warung, Yuvantinus Effrem; Momang, Hendrianus Dwianot; Sii, Petrus; Lelo Lein, Adeline (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2024)
Character education can be learned through understanding character values in monologue texts in school extracurricular activities. This research aims to describe the character education values contained in the Tangan Kecil Aini monologue script using qualitative descriptive methods. The Tangan Kecil Aini monologue manuscript is the main data source, and the data is in the form of dialogue excerpts that are relevant to the research topic. Data was collected through reading and note-taking techniques. Data analysis uses four stages: data identification, data classification, data analysis, and conclusion. The research results indicate that in this monologue script, there are 10 character education values, namely responsibility, care for the environment, hard work spirit, religiousness, discipline, creativity, curiosity, solidarity, optimism, and empathy. These values can help students understand how character values are explored in monologue texts and implemented in everyday life. Following up on these findings, research on monologue scripts can be carried out using other methods to develop students' speaking skills, stage mastery techniques, and mentality in public areas.